Correlation Analysis of Daily Exposure Duration, Carbon Monoxide Levels on Hemoglobin Levels and Erythrocyte Counts in Grilled Fish Traders in Palangka Raya - Chairunnissa, Adinda (BKM Public Health and Community Medicine, 2024)
Purpose: The process of grilling fish produces toxic carbon monoxide, inhaled continuously by grilled fish traders. If it enters the blood, it can cause a carboxyhemoglobin (COHb) reaction, so that the body produces new erythrocytes and causes erythrocytes to increase. To determine the correlation between daily exposure duration, carbon monoxide levels on hemoglobin levels, and erythrocyte counts in grilled fish traders in Palangka Raya. Method: The method used is quantitative with a cross-sectional design. Respondents are grilled fish traders who are exposed to smoke. This research will measure carbon monoxide levels in the air using a carbon monoxide meter, hemoglobin levels and erythrocyte counts using a hematology analyzer, and interview grilled fish traders about their daily exposure duration to carbon monoxide. Results: The total number of respondents who were willing to participate in this research was 42 respondents and 28 respondents were not willing, this is because respondents are not brave with needles. The daily smoke exposure duration between 5 and 19 hours (mean = 10.8; SD = 3.5). Carbon monoxide levels in burning stoves are 79% between 101 and 250 ppm, carbon monoxide levels in the facial area of ​​grilled fish traders are 55% between 50 and 100 ppm and carbon monoxide levels on the road are 100% less than 50 ppm or between 0 ppm and 17 ppm. There 19% of respondents had low hemoglobin levels and 21% of respondents had high erythrocyte counts. Conclusion: There is no correlation between carbon monoxide on hemoglobin levels and erythrocyte counts. There is a negative correlation between daily exposure duration and hemoglobin levels. Suggestions for future researchers are that blood sampling was carried out not only once, other confounding variables were analyzed and a multivariate analysis was carried out to further analyze cause and effect.